2019
DOI: 10.5582/ddt.2019.01057
|View full text |Cite
|
Sign up to set email alerts
|

Cur2004-8, a synthetic curcumin derivative, extends lifespan and modulates age-related physiological changes in <i>Caenorhabditis elegans </i>

Abstract: Curcumin, a compound found in Indian yellow curry, is known to possess various biological activities, including anti-oxidant, anti-inflammatory, and anti-cancer activities. Cur2004-8 is a synthetic curcumin derivative having symmetrical bis-alkynyl pyridines that shows a strong anti-angiogenic activity. In the present study, we examined the effect of dietary supplementation with Cur2004-8 on response to environmental stresses and aging using Caenorhabditis elegans as a model system. Dietary intervention with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…Moreover, it regulates aging, stress resistance, and immunity in C. elegans. It has been reported that daf -16 is responsible for the activation of major antioxidant machinery [35,36]. In the current study, we found that the lifespan-extension effect of SDA required daf-16.…”
Section: Sda Prolongs the Lifespan Of C Elegans By Regulating Mitocho...supporting
confidence: 62%
“…Moreover, it regulates aging, stress resistance, and immunity in C. elegans. It has been reported that daf -16 is responsible for the activation of major antioxidant machinery [35,36]. In the current study, we found that the lifespan-extension effect of SDA required daf-16.…”
Section: Sda Prolongs the Lifespan Of C Elegans By Regulating Mitocho...supporting
confidence: 62%